KUAT TARIK INTERFASE ANTARA BETON LAMA DAN BETON BARU DENGAN VARIABEL BETON GEOPOLIMER DAN BETON KONVENSIONAL - Purwanto Purwanto; Rudi Yuniarto Adi; Arum Yumastuti; Farah Diena Amelia (Jurnal Disprotek, 2020)
SCGC Concrete (Self Compacting Geopolymer Concrete) has the advantage of being easier and more effective in casting, so it can be applied to strengthening building structures, including the Concrete Jacketing method and voute / haunch beam. This reinforcement method is a form of composite concrete application with different concrete ages, which consists of existing structures with conventional concrete material and jacket or haunch section with SCGC concrete material. This study aims to determine the characteristics in the form of direct tensile strength, flexural tensile strength, and pull off tests (bond test) to test the strength of adhesion between concrete joints. Making specimens consists of 4 x 4 x 16 (cm) flexural tensile test beams, and 15 x 15 x 60 (cm) pull off specimens, and direct tensile specimens in the form of numbers 8. The principle of making test specimens is done by casting twice The first casting is done on the first half of the mold, then wait until the concrete age is 28 days. Then a second casting is carried out in the next half, until the concrete age is 28 days. So that the total age of concrete in making connection test specimens is 56 days. From the results of this study it was found SCGC concrete has a higher adhesion than conventional concrete so that SCGC concrete can be applied for structural reinforcement.